Prevention of ADHD related problems: a universal preschool program. Issue 3 (1st June 2015) - Christiansen, Hanna; Hirsch, Oliver; König, Anika; Steinmayr, Ricarda; Roehrle, Bernd
Abstract : Purpose: – Early onset of behavioral disorders is predictive of long term adverse outcomes. There are some indicated and selective early prevention programs for attention deficit/hyperactivity disorder (ADHD), one of the most common behavioral disorders in childhood and adolescence. The purpose of this paper is to present a universal preschool program for preventing the development of ADHD related symptoms for children aged three to six. Design/methodology/approach: – A total of 413 preschool children (experimental group (EG)=193; control group (CG)=220), and their teachers participated in the study. Children in the EG were randomized to two conditions: universal intervention (behavior modification (BM)=99) vs additional ADHD specific elements (BM+attention training; BM+AT=94) to evaluate effects of a universal intervention vs additional ADHD specific elements. The universal intervention trained general behavior modification (BM) techniques to enhance start behavior (i.e. following color based rules, positive participation in activities, enhancement of skills related to attentional function), and to extinguish stop behavior (i.e. hyperactive behavior such as uncontrolled running around, disturbing others, quarreling, etc.). These techniques were based on published intervention programs (Phelan and Schonour, 2004). The AT consisted of thirteen teacher led 45 minute based sessions in a small group format with an introductory play activity, 15 minutes picture based AT tasks (task analysis, action planning, action, reappraisal), a social interaction game, and a game to enhance perception of visual, auditory, olfactory, haptic, and gustatory senses. To determine effects, the Strength and Difficulties Questionnaire (SDQ) and the Behavior Rating for Preschoolers (VBV) were used. A high risk group with high scores on those measures was analyzed separately. Findings: – Children in all three groups did not differ significantly at baseline in all relevant variables (ADHD symptoms measured with the SDQ and VBV, socio-economic status (SES), gender, age: MANCOVA: F 10, 796 =1.732, p =0.07) and none of the children had a diagnosis of ADHD. After training participation, children in the EG showed significantly less ADHD related problem behavior compared to children in the CG ( F 8, 1, 506 =2.717, p =0.006); this was especially so for the high risk group ( F 4, 754 =2.60, p =0.035). Multi-level analyses revealed significant influences of age, gender, and SES on post-training symptom ratings (SDQ: t -statistic=3.03, p =0.003; VBV 3-6: t -statistic=4.151, p < 0.001). Research limitations/implications: – This is a quasi-experimental study, since due to time restriction half the preschools did not want to participate in the experimental study. Thus, participating children were not randomly assigned to the experimental and control conditions, though children were randomly assigned to two different treatments within the intervention group (EG1/EG2). Due to the design of the study and to ensure high participation rates, only preschool teachers rated children's behavior, though the predictive value of teacher ADHD symptoms exceeds parental ones. Finally, inclusion of parent training elements would most probably enhance effects. Practical implications: – General BM techniques are easily taught and seem to positively influence children's ADHD related symptoms while not harming children without such symptoms. Since studies showed that after a bogus instruction teacher expected children to exhibit ADHD symptoms and rated them as more disturbed (Rosenthal effect), a universal approach is less stigmatizing and possibly more effective, especially when interventions start early in life before symptoms result in full diagnoses. Social implications: – This study established positive universal effects, and moderate to large effects for the subgroup of high risk children with ADHD related symptoms. General behavior management in preschools might thus be a possible strategy for preventive interventions of ADHD related symptoms. Originality/value: – The is one of the first studies on a preventive ADHD preschool program. General BM techniques of this study were easily taught and implemented, and showed positive effects. Since selective and indicated interventions depend on high program fidelity, are harder to implement, and related to higher costs, general BM techniques as introduced in this study, might be an option for universal prevention strategies for ADHD related symptoms in preschool settings.